RESPON IRAN TERHADAP KEBIJAKAN COERCIVE DIPLOMACY AMERIKA SERIKAT TERKAIT ISU NUKLIR - Inda Permata Asi; Ahmad Jamaan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Iran's nuclear enrichment was initially carried out with the United States in 1957 which was marked by the existence of the Nuclear Cooperation Agreement. However, the cooperation between Iran and the United States ended at the time of the Iranian revolution in 1979. The United States assumed that Iran was making weapons of mass destruction and demanded that Iran stop its nuclear program. However, Iran continued its nuclear program. To oppose Iran's nuclear program, the United States carried out a policy of coercive diplomacy against Iran so that Iran submits to the will of the United States and Iran's nuclear program can be stopped. This paper will discuss how Iran's response in dealing with the coercive diplomacy imposed by the United States on Iran and whether or not the coercive diplomacy policy of the United States and its allies towards Iran was effective because the results of the coercive diplomacy policy carried out by the United States against Iran were not successful because there were factors The factors that make Iran still able to carry out its nuclear program such as the supply of nuclear manufacturing materials from Russia, the JCPOA agreement on the Iran nuclear program agreement and also the absence of Iran's nuclear findings that deviate by the IAEA. Keywords: America's Coercive Diplomacy , JCPOA, Iran’s nuclear